Stochastic system identification and damage detection using firefly algorithm. (1st January 2014) - Fadel Miguel, Leandro Fleck; Miguel, Letícia Fleck Fadel; Kaminski, João
Smart methods of control and structural health monitoring (SHM) for large structures are highly needed, since it refers to the implementation of in situ non-destructive sensing and analysis of the dynamic system characteristics. The aim of this implementation is to detect changes, which may indicate damage or degradation. In addition, they have the potential feature to promote a more economical management and maintenance programme, since in certain structural applications a lack of access to the damaged area imposes an additional constraint on damage identification procedures. In this paper, a new approach for vibration-based (SHM) procedures is presented, in an ambient vibration context. This method combines a time domain modal identification technique (stochastic subspace identification – SSI) with the recently proposed evolutionary firefly algorithm (FA). A series of numerical examples with different damage scenarios and noise levels have been carried out under impact and ambient vibration. Additionally, an experimental study of three cantilever beams with several different damage scenarios is conducted and the proposed methodology has shown potential for use in the damage diagnosis assessment of the remaining structural life.